Prospects for the use of biological control agents against Anoplophora in Europe. Issue 1 (14th October 2014) - Brabbs, Thomas; Collins, Debbie; Hérard, Franck; Maspero, Matteo; Eyre, Dominic
Abstract This review summarises the literature on the biological control of Anoplophora spp. (Coleoptera: Cerambycidae) and discusses its potential for use in Europe. Entomopathogenic fungi: Beauveria brongniartii Petch (Hypocreales: Cordycipitaceae) has already been developed into a commercial product in Japan, and fungal infection results in high mortality rates. Parasitic nematodes: Steinernema feltiae Filipjev (Rhabditida: Steinernematidae) and Steinernema carpocapsae Weiser have potential for use as biopesticides as an alternative to chemical treatments. Parasitoids: a parasitoid of Anoplophora chinensis Forster, Aprostocetus anoplophorae Delvare (Hymenoptera: Eulophidae), was discovered in Italy in 2002 and has been shown to be capable of parasitising up to 72% of A. chinensis eggs; some native European parasitoid species (e.g. Spathius erythrocephalus) also have potential to be used as biological control agents. Predators: two woodpecker (Piciformis: Picidae) species that are native to Europe, Dendrocopos major Beicki and Picus canus Gmelin, have been shown to be effective at controlling Anoplophora glabripennis Motschulsky in Chinese forests. The removal and destruction of infested and potentially infested trees is the main eradication strategy for Anoplophora spp. in Europe, but biological control agents could be used in the future to complement other management strategies, especially in locations where eradication is no longer possible. © 2014 Crown copyright. Pest Management Science © 2014 Society of Chemical Industry